ANALISIS ISI KONTEN YOUTUBE MENJADI MANUSIA TERHADAP KECERDASAN EMOSIONAL MASYARAKAT DI KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Wulandari , Iracrsanti; Zelfia, Zelfia; Idris, Muhammad (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This thesis discusses the Content Analysis of YouTube Content Being Human on the Emotional Intelligence of the People of Biringkanaya District. The main problem is whether content analysis (physical unit) has an effect on the emotional intelligence of the people of Biringkaya District, Makassar City. The type of research used is quantitative content analysis. This researchlasted for one month, located in the Biringkanaya sub-district, Makassar City, with the informants from the Biringkanaya District community itself. The results showed that after the researchers conducted an analysis of the two variables, the researchers found that 52.6% of the people of Biringkanaya District, Makassar City "Less Agree"that the duration of a video can affect emotional intelligence, the physical unit variable in the analysis has no effect on emotional intelligence of the community in Biringkanaya District, Makassar City.